The Experiences of Mother who has Children with Autism (Indonesian Journal of Early Childhood Education Studies, 2022)
Purpose. This study aimed to determine the experience of mothers who have autistic children. Methods. This qualitative research applied the phenomenological method. The subjects in this study were three early adult mothers with children with autism. A semi-structured interview was used as the data collection method. This study used Interpretative Phenomenological Analysis (IPA) for the data analysis technique. Findings. The results showed that there were 3 main themes: 1) emotional fluctuations (sad, angry, disappointed, worried), 2) parenting for autistic children (mothers experienced stress (easily getting tired, problem-solving disorders, helplessness, behavioral disorders)), and 3) planning for the children's future (professional care, special schools, autism communities). Keywords: Mother's experience; children; autism